Entry Modes of MNCs in a foreign market – A Case Study of Starbucks in China - Damrongratanasilp, Jidapa (2017)
Nowadays, many companies are moving from domestic markets to international markets because the competition in domestic markets has significantly increased due to globalization. However, the most concerning issue for multinational companies before entering a foreign market is the decision of entry mode because the entry mode strategy can have a huge impact on the success of the companies in a new market. In addition, the entry mode decision of the companies can be influenced by a number of factors such as firm size, international experience of firm, cultural distance, market barriers, and country risks. Thus, before choosing the entry mode strategy, the companies have to analyze those influential factors because those factors can affect the companies’ performance. This study has examined the factors that influenced the entry mode decision of Starbucks when the company entered China in order to know the factors that affected the Starbucks’ entry mode choice and what entry mode strategy did Starbucks use in China. Additionally, the data that was used to analyze in this study has been collected through a qualitative method by using books, literature, journals, and internet resources. Lastly, this study has found several influential factors which were divided into external and internal factors. Starbucks’ entry mode choice was affected by both factors. However, the external factors were more influential than the internal factors.